2021
DOI: 10.1016/j.icarus.2021.114451
|View full text |Cite
|
Sign up to set email alerts
|

Tidal pull of the Earth strips the proto-Moon of its volatiles

Abstract: Prevailing models for the formation of the Moon invoke a giant impact between a planetary embryo and the proto-Earth (Canup 2004;Ćuk et al. 2016). Despite similarities in the isotopic and chemical abundances of refractory elements compared to Earth's mantle, the Moon is depleted in volatiles (Wolf and Anders 1980). Current models favour devolatilisation via incomplete condensation of the proto-Moon in an Earth-Moon debris-disk (Charnoz and Michaut 2015;Canup et al. 2015;Lock et al. 2018). However the physics o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
37
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 83 publications
2
37
1
Order By: Relevance
“…In that scenario, MVEs are lost incrementally at a temperature of ∼1600-1800 K. Tang & Young (2020) made the case that the vapor generated would have the opportunity to equilibrate with the surface of the magma ocean, thereby limiting escape efficiency and isotopic fractionation. Charnoz et al (2021) showed, however, that tidal pull from Earth would have been able to sustain a vigorous hydrodynamic escape flow that could Canup et al (2015). In that model, a proto-Moon representing ∼40% of the final lunar mass is rapidly formed beyond the Roche limit.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…In that scenario, MVEs are lost incrementally at a temperature of ∼1600-1800 K. Tang & Young (2020) made the case that the vapor generated would have the opportunity to equilibrate with the surface of the magma ocean, thereby limiting escape efficiency and isotopic fractionation. Charnoz et al (2021) showed, however, that tidal pull from Earth would have been able to sustain a vigorous hydrodynamic escape flow that could Canup et al (2015). In that model, a proto-Moon representing ∼40% of the final lunar mass is rapidly formed beyond the Roche limit.…”
Section: Discussionmentioning
confidence: 98%
“…(3) Sossi et al (2019) and Charnoz et al (2021) considered a model involving loss of MVE from the LMO by hydrodynamic escape facilitated by the tidal pull of Earth (Figure 11(c)). In that scenario, MVEs are lost incrementally at a temperature of ∼1600-1800 K. Tang & Young (2020) made the case that the vapor generated would have the opportunity to equilibrate with the surface of the magma ocean, thereby limiting escape efficiency and isotopic fractionation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations